2013
DOI: 10.1007/s10815-013-0007-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of micro-vibration culture system on embryo development

Abstract: Purpose Micro-vibration culture system was examined to determine the effects on mouse and human embryo development and possible improvement of clinical outcomes in poor responders. Materials and methods The embryonic development rates and cell numbers of blastocysts were compared between a static culture group (n=178) and a micro-vibration culture group (n=181) in mice. The embryonic development rates and clinical results were compared between a static culture group (n=159 cycles) and a micro-vibration culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…Thus, while changing or " refreshing " medium during culture would be of benefi t should it prove necessary to remove harmful waste products and replenish diminished substrates, such steps might eliminate any positive effects of accumulated embryo-derived developmentenhancing factors. Alternatives (reviewed by Swain & Smith, 2011) include dynamic culture systems such as tilting (Matsuura et al, 2010;Hara et al, 2013) and micro-vibrating (Hur et al, 2013) culture systems, and microfl uidics (reviewed by da Rocha & Smith, 2012), all of which have yet to be fully developed and evaluated.…”
Section: Expert Contributionsmentioning
confidence: 99%
“…Thus, while changing or " refreshing " medium during culture would be of benefi t should it prove necessary to remove harmful waste products and replenish diminished substrates, such steps might eliminate any positive effects of accumulated embryo-derived developmentenhancing factors. Alternatives (reviewed by Swain & Smith, 2011) include dynamic culture systems such as tilting (Matsuura et al, 2010;Hara et al, 2013) and micro-vibrating (Hur et al, 2013) culture systems, and microfl uidics (reviewed by da Rocha & Smith, 2012), all of which have yet to be fully developed and evaluated.…”
Section: Expert Contributionsmentioning
confidence: 99%
“…Regarding the effect of micro-vibration on high-quality embryos and clinical pregnancy rates, when the embryos were cultured using MVC system at a frequencies between 20 and 44 Hz, the number of high-quality embryos and pregnancy rates increased significantly at each stage compared with those in the SC system [11,23]. Furthermore, Hur et al [9] found that rates of blastocyst development on day 5, pregnancy, and implantation were increased with the MVC system compared with the SC system in poor responder patients. Positive effects of mechanical micro-vibration have been shown in our previous study of IVM cycles [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, the in vivo oocytes and embryos move continuously because of ciliary beating accompanied by the contractions of the uterus and fallopian tubes. Thus, they are physically affected by mechanical forces or stimuli such as shear stress, kinetic friction forces, and vibration [8,9]. Recently, studies of human embryos using a micro-vibration culture (MVC) system based on vibrations of 5-20 Hz generated by ciliated epithelium cells of oviduct revealed that during in vitro culture (IVC), the mechanical stimulation of embryos increased the implantation, pregnancy, and live birth rates compared with the SC system [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the failure of static culture systems to mimic the dynamic fluid environment in the fallopian tube [136], dynamic culture platforms that explored shaking/rotation [137], controlled fluid flow [138] and vibration [139] models were studied for use in embryonic development where method of coculturing embryos with endometrial was done to overcome developmental arrest of early embryos in single culture. Although these methods showed enhanced perform-ance and beneficial effects of coculturing on the development of mammalian, they could not be considered as a complete on chip system for womb.…”
Section: Breast and Womb On Chipmentioning
confidence: 99%